A comprehensive evaluation of commercial activated carbon for key gasoline vapor removal based on the improved AHP method - Hu, Wei; Ren, Biqi; Lu, Dan; Li, Beibei; Liu, Jia; Liang, Wenjun; Huang, Yuhu (Journal of environmental chemical engineering, 2024)
Adsorption technology is considered one of the most effective methods for removing volatile organic compounds (VOCs). However, it is difficult to select the optimal activated carbon (AC) for different VOCs industries due to its various categories. To develop a comprehensive assessment system for commercial AC in typical gasoline vapor removal, 12 commercial AC (coal, shell, and wood carbon) were selected. Their physical properties, chemical characteristics and target pollutant adsorption capacity were studied. A comprehensive evaluation system was established based on the improved Analytic Hierarchy Process (AHP). The weighted of AHP method was determined by the correlation between adsorption capacity and each property indicator. The adsorption of i-pentane was influenced by the specific surface area （SSA） and alkaline functional groups of AC, with the former showing a significant positive correlation (correlation coefficient=0.853, P＜0.05) and the latter showing a negative correlation (correlation coefficient=−0.845, P＜0.05). Based on the average comprehensive scores, the wooden carbon performed the best, followed by the coal carbon and the shell carbon. Owing to the highest SSA (1851 m2/g) and the highest acidic functional groups (1.354 mmol/g) of the wooden carbon, the i-pentane adsorption performance (553.5 mg/g) was the best. The method we proposed can be used to rank the commercial AC based on the different aspects, which can be employed for the selection and recommendation of high-quality AC for various VOCs industries. [Display omitted] •The physical, chemical characteristics of AC and the adsorption properties of i-pentane were studied.•A comprehensive evaluation system is utilized to select high-quality AC.•The improved AHP method considers both positive and negative weights.•Spearman correlation was used to assess the connections among AC properties.